Effects of the alcoholic extract of ginseng roots and carob fruits in comparison with vitamin E in improving the efficiency of the male reproductive system of albino rabbits - Qays Assi Ahmed; Sami Ibrahim Abdullah; Huda Mawlood Taher (Caspian Journal of Environmental Sciences)
Scientists have been interested in human reproduction for a long time, since on the one hand, it is related to human life, and on the other hand, it ensures the transmission of genetic traits from parents to children, as low fertility is considered one of the social problems leading to psychological disorders in couples who are unable to have children or what is called infertile. Therefore, this study aimed to find out the protective effects of the alcoholic extract of ginseng roots and carob fruits on the level of oxidative balance in semen and improving reproductive efficiency by examining the histological parameters of testes in albino male rabbits, and comparing these effects with the effects of vitamin E known for its antioxidant properties. This study included using forty adult albino male rabbits in eight groups, with five rabbits in each group and convergent weights. All groups were fed a standard diet throughout the five-month experimental period. The treatments were as follows: The first group (T1) were gavaged by distilled water, the second (T2) by 200 mg kg-1 alcoholic extract of ginseng roots, the third (T3) by 400 mg kg-1 alcoholic extract of ginseng roots , the fourth (T4) by 200 mg kg-1 alcoholic extract of carob fruits, the fifth (T5) by 400 mg kg-1 alcoholic extract of carob fruits, the sixth (T6) by 100 mg kg-1 alcoholic extract of ginseng roots + 100 mg kg-1 carob fruits, the seventh (T7) by 200 mg kg-1 alcoholic extract of ginseng roots + 200 mg kg-1 carob fruits, and finally, the eighth (T8) by 400 mg kg-1 vitamin E. Our results showed a significant drop (p < 0.05) in the level of MDA concentration and a significant upraise in the level of CAT, GSH and TAC concentration in the semen. The results also revealed the normal shape of the seminiferous tubules and an improvement in reproductive efficiency through the elevation in spermatogenesis percentage (SP), primary spermatocytes percentage (PSP), secondary spermatocytes percentage (SSP), spermatozoa percentage (SpP) and mature sperm percentage (MSP) for groups dosed by ginseng root extract + carob fruits and by vitamin E compared to the normal control group. Ginseng roots extract at a dose of 200 mg kg-1 + carob fruits at a dose of 200 mg kg-1 (T7) were superior to all treatments, followed by vitamin E (T8). Thus, we concluded from the current study that the effect of T7 reduces the level of free radicals and raises the level of antioxidants in the semen, and increases reproductive efficiency through the high percentage of sperm in the semen.